2009
DOI: 10.2174/1876503300902010189
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Aluminum in Hydrochloric Acid Solution Using Potassium Iodate Inhibitor

Abstract: Abstract:The inhibition effect of potassium iodate on the corrosion of aluminum in 2M HCl has been studied by weight loss, polarization and electrochemical impedance spectroscopy (EIS) measurements. It has been found that KIO 3 acts as an excellent inhibitor. Inhibition efficiency with 100 ppm inhibitor was very high. Polarization curves reveal that the used inhibitor is a mixed type inhibitor. The surface adsorption of KIO 3 leads to a decrease of double layer capacitance as well as an increase of polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…The inductive loop is generally attributed to the relaxation process in the oxide film covered on metal surface [26]. The reasons behind the deviations from perfect semicircles are usually involved with the frequency dispersion of interfacial impedance, which can be attributed to various kinds of physical phenomena such as active sites, surface roughness, and non-homogeneity of the solids [27]. The diameter of the capacitive loop is enlarging gradually with increasing concentrations of inhibitor, indicating that the charge transfer resistance is increased and the adsorbed inhibitor forms a more compact monolayer on metal surface with an increasing amount of inhibitor.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…The inductive loop is generally attributed to the relaxation process in the oxide film covered on metal surface [26]. The reasons behind the deviations from perfect semicircles are usually involved with the frequency dispersion of interfacial impedance, which can be attributed to various kinds of physical phenomena such as active sites, surface roughness, and non-homogeneity of the solids [27]. The diameter of the capacitive loop is enlarging gradually with increasing concentrations of inhibitor, indicating that the charge transfer resistance is increased and the adsorbed inhibitor forms a more compact monolayer on metal surface with an increasing amount of inhibitor.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…They are used as reaction vessels, pipes, machinery and chemical batteries because of their advantages; low cost, lightness and good corrosion resistance at moderate temperatures [1,2,3]. It has been reported that passive oxide film formed on aluminium surface is responsible for its resistance to corrosion, but the surface film is amphoteric and dissolves substantially when the metal is exposed to high concentrations of acids or basses [2,4]. Aluminium dissolves readily in hydrochloric acid to form aluminium chloride and hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic chemical substances have been used for the corrosion inhibition of aluminium in corrosive media. The inhibition effect of potassium iodate on the corrosion of aluminium in HCl has been reported [2]. Weight loss, polarization and impedance spectroscopy techniques were employed in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported good correlation between this technique and gasometric, impedance, and polarisation techniques [16][17][18][19][20]. The corrosion rate of aluminium in HCl at 60 ∘ C ( Figure 2) increased at a rate which decreased with exposure time and was maximum at 8.6 × 10 −2 mm/yr at 10 hours.…”
Section: Corrosion Ratesmentioning
confidence: 87%
“…For the calculation of corrosion rates, the relationship in (1) as described by Jones [1] and other authors [15][16][17] was employed CR = 87.6Δwt…”
Section: Corrosion Ratesmentioning
confidence: 99%